2010
DOI: 10.1038/labinvest.2010.102
|View full text |Cite
|
Sign up to set email alerts
|

Sphinganine-1-phosphate protects kidney and liver after hepatic ischemia and reperfusion in mice through S1P1 receptor activation

Abstract: Liver failure due to ischemia and reperfusion (IR) and subsequent acute kidney injury are significant clinical problems. We showed previously that liver IR selectively reduced plasma sphinganine-1-phosphate levels without affecting sphingosine 1-phosphate (S1P) levels. Furthermore, exogenous sphinganine 1-phosphate protected against both liver and kidney injury induced by liver IR. In this study, we elucidated the signaling mechanisms of sphinganine 1-phosphate-mediated renal and hepatic protection. A selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 53 publications
2
58
0
Order By: Relevance
“…S1P may serve a key function during the induction of torpor by regulating additional aspects of the immune system as well as other physiological changes that are not related primarily to immune function (30). Not only does S1P regulate the function of other types of leukocytes (31); it also is involved in other biological processes (32) and is implicated in governing protection against ischemia/reperfusion-induced injury in brain, heart, liver, and kidney (33)(34)(35)(36). Therapeutic hypothermia is used in patients with clinical conditions such as cardiac arrest and brain trauma and in patients undergoing cardiac or brain surgery because reducing cerebral metabolism has neuroprotective properties in periods of low oxygen supply (9).…”
Section: Discussionmentioning
confidence: 99%
“…S1P may serve a key function during the induction of torpor by regulating additional aspects of the immune system as well as other physiological changes that are not related primarily to immune function (30). Not only does S1P regulate the function of other types of leukocytes (31); it also is involved in other biological processes (32) and is implicated in governing protection against ischemia/reperfusion-induced injury in brain, heart, liver, and kidney (33)(34)(35)(36). Therapeutic hypothermia is used in patients with clinical conditions such as cardiac arrest and brain trauma and in patients undergoing cardiac or brain surgery because reducing cerebral metabolism has neuroprotective properties in periods of low oxygen supply (9).…”
Section: Discussionmentioning
confidence: 99%
“…We detected apoptosis after renal IR with terminal deoxynucleotidyl transferase dUTPmediated nick-end labeling (TUNEL) staining as described elsewhere (41) by using a commercially available in situ cell death detection kit (Roche, Indianapolis, IN) according to the instructions provided by the manufacturer. Kidney inflammation after renal IR was assessed by detection of neutrophil infiltration using immunohistochemistry 24 h after IR as described previously (41). Neutrophils infiltrating the kidney were quantified in 5-7 randomly chosen ϫ400 microscope image fields in the corticomedullary junction, and results are expressed as neutrophils counted per ϫ400 field.…”
Section: Methodsmentioning
confidence: 99%
“…The expression and activity of sphingosine kinase have been detected in the kidneys (1, 10) and the mRNAs of S1P receptors are also present in the kidneys (17). It has been shown that S1P protects the kidneys from ischemic injury (2,27). It has also been demonstrated that S1P regulates vascular functions (14, 23).…”
mentioning
confidence: 99%